Serologic and Cytokine Signatures in Children With Multisystem Inflammatory Syndrome and Coronavirus Disease 2019. (24th February 2022) - Lapp, Stacey A; Abrams, Joseph; Lu, Austin T; Hussaini, Laila; Kao, Carol M; Hunstad, David A; Rosenberg, Robert B; Zafferani, Marc J; Ede, Kaleo C; Ballan, Wassim; Laham, Federico R; Beltran, Yajira; et al.
Abstract: Background: The serologic and cytokine responses of children hospitalized with multisystem inflammatory syndrome (MIS-C) vs coronavirus disease 2019 (COVID-19) are poorly understood. Methods: We performed a prospective, multicenter, cross-sectional study of hospitalized children who met the Centers for Disease Control and Prevention case definition for MIS-C (n = 118), acute COVID-19 (n = 88), or contemporaneous healthy controls (n = 24). We measured severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike receptor-binding domain (RBD) immunoglobulin G (IgG) titers and cytokine concentrations in patients and performed multivariable analysis to determine cytokine signatures associated with MIS-C. We also measured nucleocapsid IgG and convalescent RBD IgG in subsets of patients. Results: Children with MIS-C had significantly higher SARS-CoV-2 RBD IgG than children with acute COVID-19 (median, 2783 vs 146; P < .001), and titers correlated with nucleocapsid IgG. For patients with MIS-C, RBD IgG titers declined in convalescence (median, 2783 vs 1135; P = .010) in contrast to patients with COVID-19 (median, 146 vs 4795; P < .001). MIS-C was characterized by transient acute proinflammatory hypercytokinemia, including elevated levels of interleukin (IL) 6, IL-10, IL-17A, and interferon gamma (IFN-γ). Elevation of at least 3 of these cytokines was associated with significantly increased prevalence of prolonged hospitalization ≥8 days (prevalence ratio, 3.29 [95% CI, 1.17–9.23]). Conclusions: MIS-C was associated with high titers of SARS-CoV-2 RBD IgG antibodies and acute hypercytokinemia with IL-6, IL-10, IL-17A, and IFN-γ.